Controversies in the treatment of paediatric immune thrombocytopenia - Rubén Berrueco; José Luis Dapena; Elena Sebastián; Ana Sastre (Elsevier, 2018)
Immune thrombocytopaenia (ITP) is a relatively common disorder in childhood. Although it usually achieves spontaneous remission at this age, the management of persistent or chronic ITP in children is still controversial. The aim of this article is to address current controversies related to the treatment of persistent, chronic, and refractory ITP in children, including the role of rituximab and splenectomy, as well as focusing on a new approach with thrombopoietin receptor agonists (TPO-RAs). Eltrombopag and romiplostim are safe and useful drugs for paediatric ITP. These two TPO-RAs might delay surgery and other treatments such as rituximab. However, the potential side effects described in adult patients should be considered. Paediatric patients with refractory ITP, undergoing new treatments, should be supervised in specialised centres. Resumen: La trombocitopenia inmune (PTI) es una entidad relativamente frecuente en pediatría. Aunque su evolución suele ser favourable en la mayoría de los casos, el manejo de aquellos pacientes en los que la enfermedad persiste es muy controvertido. Este artículo pretende, a través de una revisión de la literatura más reciente, responder a aspectos relacionados con el tratamiento de la PTI persistente, crónica y refractaria durante la infancia, haciendo especial énfasis en el papel del rituximab, la esplenectomía y los análogos de la trombopoyetina (ar-TPO) en la infancia. La aparición de los ar-TPO (eltrombopag y romiplostim) amplía el arsenal terapéutico de la PTI pediátrica. Además, tras haber demostrado un perfil de seguridad adecuado en ensayos clínicos, retrasa la indicación de esplenectomía o el uso de tratamientos asociados a mayor riesgo de complicaciones, como rituximab. No obstante, se recomienda que su manejo sea supervisado por centros con experiencia de cara a monitorizar complicaciones potenciales a medio y largo plazo ya descritas en el paciente adulto.